Helping or Hurting? The Efficacy of Municipal Bankruptcy. (16th May 2021) - Abott, Carolyn; Singla, Akheil
Abstract: Local governments facing extreme fiscal stress have few options. One that has historically been rare is filing for Chapter 9 bankruptcy. The limited number of cases has prevented any systematic study of municipal bankruptcy. But given the results of bankruptcy for individuals, there are reasons to believe that bankruptcy can provide a fresh financial start for local governments. This study leverages six municipal bankruptcies in the years immediately following The Great Recession to explore the effects of bankruptcy on local governments ' financial health. It employs a variety of empirical approaches to generate a counterfactual for the bankrupt governments and assess the effects of bankruptcy: synthetic control, propensity‐score matching, staggered difference‐in‐differences, and an event study. The results show that bankruptcy is associated with no declines and some meaningful improvements in financial health. These findings suggest that Chapter 9 bankruptcy may provide extremely stressed local governments with a potential path forward.